2021
DOI: 10.1101/2021.06.25.449513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ketamine and sleep modulate neural complexity dynamics in cats

Abstract: There is increasing evidence that level of consciousness can be captured by neural informational complexity: for instance, complexity, as measured by the Lempel Ziv (LZ) compression algorithm, decreases during anesthesia and non-rapid eye movement (NREM) sleep in humans and rats, when compared to LZ in awake and REM sleep. In contrast, LZ is higher in humans under the effect of psychedelics, including subanesthetic doses of ketamine. However, it is both unclear how this result would be modulated by varying ket… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
1
4
0
Order By: Relevance
“…Our findings corroborate previous research which demonstrated that the spectral slope and neural complexity are sensitive markers of sleep depth (Abásolo et al, 2015; Bódizs et al, 2021; Lendner et al, 2020; Pascovich et al, 2022; Schartner et al, 2017; Tagliazucchi et al, 2013). Building upon these findings, we leveraged repeated EEG recordings per subject and confirmed that the two parameters can robustly differentiate all sleep stages from wakefulness.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings corroborate previous research which demonstrated that the spectral slope and neural complexity are sensitive markers of sleep depth (Abásolo et al, 2015; Bódizs et al, 2021; Lendner et al, 2020; Pascovich et al, 2022; Schartner et al, 2017; Tagliazucchi et al, 2013). Building upon these findings, we leveraged repeated EEG recordings per subject and confirmed that the two parameters can robustly differentiate all sleep stages from wakefulness.…”
Section: Discussionsupporting
confidence: 92%
“…Since this result, others have shown that the complexity of spontaneous neural activity, as measured by LZ, can distinguish between sleep states, 2 and increases above the level of normal resting state (RS) during an altered state of consciousness due to psychoactive drugs, such as LSD. [4][5][6] These results have provided a striking impetus for the continued development of consciousness science, since they are robust and highly reproducible. However, despite these successes, progress in the science of conscious level has been limited in recent years for a number of reasons.…”
Section: Introductionmentioning
confidence: 82%
“…Since this result, others have shown that the complexity of spontaneous neural activity, as measured by LZ, can distinguish between sleep states, 2 and increases above the level of normal resting state (RS) during an altered state of consciousness due to psychoactive drugs, such as LSD. 46…”
Section: Introductionmentioning
confidence: 99%
“…We aim to add to the characterization of the interaction between psychedelic states and perturbational states in intracranial recordings and via dose-dependent manner because our own work suggests a modulation by task (Mediano et al, 2020(Mediano et al, , 2021 while others do not (Farnes et al, 2020). Accordingly (Pascovich et al, 2019), the following hypotheses were proposed: (1) LZ would reflect sleep level: LZ in wakefulness would be just above REM sleep. REM sleep would be above light sleep (LS), and NREM sleep would have the lowest complexity value; (2) LZ would be increased during the initial period of drug infusion compared with baseline wakefulness;…”
Section: Introductionmentioning
confidence: 99%